Erratum to “Short-term responses of breeding songbirds to a gradient of broadleaf removal in managed mixedwood forests in British Columbia, Canada” [618 (2026) 123918] - Leonard Patterson; Juan Andrés Martínez-Lanfranco; Ryan Jackalin; Erin Hall; Kari Stuart-Smith; Erin Bayne (Forest Ecology and Management, 2026)

Short-term responses of breeding songbirds to a gradient of broadleaf removal in managed mixedwood forests in British Columbia, Canada - Leonard Patterson; Juan Andrés Martínez-Lanfranco; Ryan Jackalin; Erin Hall; Kari Stuart-Smith; Erin Bayne (Forest Ecology and Management, 2026)

Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Integrating α and β diversity in conservation planning - Siqi P. Liang; Binbin V. Li; Ryan M. Huang; Stuart L. Pimm (Conservation Biology, 2026)
Conservation planning has long prioritized local species richness (α diversity) but has rarely explicitly integrated species turnover (β diversity) into actionable strategies. Areas with high species turnover lack recognition and protection despite their ecological importance. We devised a simple, standardized, and scalable approach for mapping species turnover. We rasterized species ranges, then counted the range edges of each species in each grid cell. This approach enables high‐resolution mapping across regions and facilitates the integration of β diversity into conservation planning. We applied this approach to the Eastern Himalayas, where 3 biodiversity hotspots abut, and used endemic bird species as our focal taxa. Our analyses revealed differences between areas of high species richness and high species turnover. Areas of high species richness were concentrated in montane forests, whereas areas of high species turnover tended to be low in mountain forests and peak in foothills and tree lines. Both areas of high species richness and high species turnover are inadequately protected. We contend that species turnover is a critical, complementary metric to species richness in understanding patterns of biodiversity. In addition, areas of high species turnover host unique species assemblages and face a dual challenge. They host peripheral populations that are more prone to local extinction, and communities within them are particularly sensitive to climate change. These vulnerabilities heighten the urgency of protecting such areas. As conservation planning evolves toward more holistic strategies that address multiple interconnected environmental challenges—such as biodiversity loss, climate change, and water security—it becomes increasingly imperative to integrate both α and β diversity into biodiversity mapping. This integration provides a more representative and ecologically robust foundation for long‐term conservation planning.

The geochemical and isotopic composition of the Miocene Vestfirðir basalts, Northwest Iceland: Tracking the evolution of the Iceland mantle plume - Ugur Balci; Emma Martin-Roberts; Björn Hardarson; J. Godfrey Fitton; Valerie Olive; Ryan Ickert; Darren F. Mark; Finlay M. Stuart (Chemical Geology, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Tropics to the Poles: A Snapshot of Coastal Eukaryotic Marine Microalgal Diversity Across Five Ecoregions - Jacqui Stuart; Ken G. Ryan; John K. Pearman; Natalie Robinson; Svenja Halfter; Jacob Thomson‐Laing; Laura Biessy; Kirsty F. Smith (Molecular Ecology, 2025)
Eukaryotic microalgae are key organisms in marine environments, contributing to essential nutrient and biogeochemical cycles. Climate change is already causing shifts in the composition and diversity of microalgal assemblages, with coastal ecosystems experiencing increased pressure. Molecular techniques, such as environmental DNA (eDNA) metabarcoding, have allowed eukaryotic microalgal communities (EMCs) to be characterised more rapidly than traditional methods, addressing some data gaps. Many geographic regions still lack comprehensive baseline assessments of entire EMCs, often focusing on specific taxonomic or functional groups. In this study, we used eDNA metabarcoding of the 18S V9 gene region to characterise EMCs across a latitudinal gradient spanning five ecoregions from the South Pacific to the Ross Sea. Temperate sites had the highest alpha diversity and the most distinct EMCs across all ecoregions. Community composition showed clear latitudinal gradients, with a shift from dinoflagellate‐dominant EMCs at lower latitudes to diatom‐dominant EMCs at higher latitudes. The formation of EMCs was influenced by similar habitats/conditions (homogeneous selection) and proximity (homogenising dispersal) within ecoregions, while variable conditions (variable selection) and limited interconnectivity (dispersal limitation) were more prevalent between ecoregions. This snapshot of coastal EMC diversity across five ecoregions highlights distinct latitudinal patterns in community composition, with temperate regions showing higher diversity compared to polar areas. These findings provide a useful baseline for future monitoring and can help guide assessments of potential changes in microalgal communities due to climate change.

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

New Zealand Myrtaceae are susceptible to a strain from the Eucalyptus biotype of Austropuccinia psidii present in South America - Julia Soewarto; Carlos Pérez; Michael Bartlett; Chanatda Somchit; Beccy Ganley; Roanne Sutherland; Sofía Simeto; Jane E. Stewart; Jorge R. Ibarra Caballero; Stuart Fraser; Peter M. Scott; Jayanthi Nadarajan; et al. (Biological Invasions, 2025)
The international spread of the myrtle rust pathogen, Austropuccinia psidii , can be largely attributed to the “pandemic” biotype that has more than 450 host species. However, within South America, the putative native range of A. psidii , multiple biotypes have been characterised, each with a restricted known number of hosts. These biotypes may pose a significant biosecurity threat to countries already affected by the pandemic biotype. Here, we report the susceptibility of four species of Myrtaceae from New Zealand, pōhutukawa ( Metrosideros excelsa ), mānuka ( Leptospermum scoparium ), kānuka ( Kunzea ericoides ), and rawiri mānuka ( Kunzea ericoides ‘gumland ecotype’), to a strain of the Eucalyptus biotype of A. psidii . Symptoms and signs developed on inoculated plants of all species. Qualitative resistance phenotypes, with no disease development, were observed for all four species. However, no hypersensitive responses were observed. As seen for other biotypes, pōhutukawa had the greatest susceptibility, while kānuka had the lowest. These findings are consistent with prior work, showing that the Eucalyptus biotype can infect a broader range of species than its field host association implies. As well as uredinia (asexual spores), telia (sexual spores) developed on several plants, indicating that these species could provide a universal host for sexual reproduction and outcrossing between biotypes. Knowledge that the Eucalyptus biotype of A. psidii is virulent on several indigenous New Zealand Myrtaceae will inform future biosecurity risk assessments. These findings highlight the need to develop diagnostics tools to differentiate between biotypes and allow rapid responses to potential future incursions.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Associations between MASLD, atrial fibrillation, cardiovascular events, mortality and aspirin use in older adults - Daniel Clayton-Chubb; Stuart K. Roberts; Ammar Majeed; Robyn L. Woods; Andrew M. Tonkin; Mark R. Nelson; Andrew T. Chan; Joanne Ryan; Cammie Tran; Alexander Hodge; John S. Lubel; Hans G. Schneider; et al. (GeroScience, 2024)

Combining the uncombinable: corporate memories, ethnobiological observations, oceanographic and ecological data to enhance climatic resilience in small-scale fisheries - Isabel Garibay-Toussaint; Carolina Olguín-Jacobson; C. Brock Woodson; Nur Arafeh-Dalmau; Jorge Torre; Stuart Fulton; Fiorenza Micheli; Ryan O’Connor; Magdalena Précoma-de la Mora; Arturo Hernández-Velasco; Nemer E. Narchi (Frontiers in Marine Science, 2024)
The global food production system is increasingly strained by abrupt and unpredictable weather events, which hinder communities' ability to adapt to climate variations. Despite advances in meteorological predictions, many communities lack the academic knowledge or infrastructure to interpret these complex models. This gap highlights the need for solutions that make climate forecasts more accessible and actionable, especially for communities reliant on natural resources. This study explores the potential of enhancing seasonal climate forecasts by integrating local ecological knowledge (LEK) with scientific data. Specifically, we combined ethnobiological information gathered between 2022 and 2024 with existing oceanographic and ecological data to create an ethnobiological calendar for four fishing cooperatives. An ethnographic approach was used to understand the population's ethnobiological knowledge and their perceptions of marine heatwaves and climate change impacts. Coastal monitoring data was collected using moorings that recorded temperature over a 14-year period (2010–2024). To characterize giant kelp dynamics, we used an existing dataset of multispectral Landsat images, which estimates the surface canopy biomass of giant kelp forests. Ecological monitoring was conducted annually every summer from 2006 to 2023 to record the in situ abundance of ecologically and economically important invertebrate and fish species. Combining oceanographic, ecological, and ethnographic data, allowed for alligning fishers' observations with recorded marine heatwave events and ecological shifts. Our findings revealed that these observations closely matched documented marine heatwave data and corresponding ecological changes. The integration of LEK with scientific oceanographic data can significantly improved our understanding of dynamic climate regimes, offering contextually relevant information that enhances the reliability and utility of seasonal climate forecasts. By incorporating yearly data into an ethnobiological calendar, we promote more inclusive, community-based approaches to environmental management, advocating for the integration of LEK in climate adaptation efforts, emphasizing its crucial role in strengthening resilience strategies against climatic shocks.

Local elephant movements, turning angles, and water access across a rainfall gradient in Southern Africa - Jessica R. Bucciarelli; Stuart L. Pimm; Ryan M. Huang; Michael J. Chase; Keith Leggett; Armanda D. Bastos; Rudi J. van Aarde (Biological Conservation, 2024)

Diversity in bread and durum wheat stigma morphology and linkage of increased stigma length to dwarfing gene Rht14 - Margaret Pallotta; Takashi Okada; Stuart Roy; Allison Pearson; Ute Baumann; Ryan Whitford (Theoretical and Applied Genetics, 2024)
Key message The dwarfing allele Rht14 of durum wheat associates with greater stigma length, an important trait for hybrid breeding, whilst major dwarfing alleles Rht-B1b and Rht-D1b showed little to no effect. Abstract Although much understudied in wheat, the stigma is a crucial component for attaining grain set, the fundamental basis for yield, particularly in hybrid production systems where successful grain set relies on wind-driven pollen dispersal by the male parent and effective pollen capture by the female parent. Females with long stigma that exsert early are thought to be advantageous. Using glasshouse-grown lines, we examined variation in Total Stigma Length (TSL) across diverse panels comprising 27 durum and 116 bread wheat genotypes. Contrasting genotypes were selected for population development and genetic analysis. Quantitative trait loci (QTL) analysis was performed on a durum F 2 population and a bread wheat recombinant inbred line (RIL) population. Contrasting with studies of anther length, we found no large effect on TSL of the GA-insensitive semi-dwarfing genes Rht-B1 and Rht-D1 in either durum or bread wheat. However, in durum cultivar Italo, we identified a region on chromosome 6A which is robustly associated with larger TSL and contains the Rht14 allele for reduced plant height, a trait that is favourable for female line development in hybrid systems. This dual effect locus explained 25.2 and 19.2% of TSL phenotypic variation in experiments across two growing seasons, with preliminary results suggesting this locus may increase TSL when transferred to bread wheat. In a bread wheat, RIL population minor QTL on 1A and 2A was indicated, but the strongest association was with Ppd-B1 . Methods developed here, and the identification of a TSL-enhancing locus provides advances and further opportunities in the study of wheat stigma.

Mapping functional diversity of canopy physiological traits using UAS imaging spectroscopy - Emiliano Cimoli; Arko Lucieer; Zbyněk Malenovský; William Woodgate; Růžena Janoutová; Darren Turner; Ryan S. Haynes; Stuart Phinn (Remote Sensing of Environment, 2024)

Region‐wide retreats from lower elevations of range‐restricted birds across the Northern Andes - Wilderson Medina; Ryan M. Huang; Stuart L. Pimm (Conservation Biology, 2023)
Local studies show upslope shifts in the distribution of tropical birds in response to warming temperatures. Unanswered is whether these upward shifts occur regionally across many species. We considered a nearly 2000‐km length of the Northern Andes, where deforestation, temperature, and extreme weather events have increased during the past decades. Range‐restricted bird species are particularly vulnerable to such events and occur in exceptionally high numbers in this region. Using abundant crowd‐sourced data from the Cornell Lab of Ornithology database, eBird, and the Global Biodiversity Information Facility, we documented distributions of nearly 200 such species. We examined whether species shifted their elevational ranges over time by comparing observed versus expected occurrences below a low elevational threshold and above a high elevational threshold for 2 periods: before and after 2005. We predicted fewer observations at lower elevations (those below the threshold) and more at upper elevations (those above the threshold) after 2005. We also tested for deforestation effects at lower elevations within each species’ distribution ranges. We compared relative forest loss with the differences between observed and expected occurrences across the elevational range. Species’ retreats from lower elevations were ubiquitous and involved a 23–40% decline in prevalence at the lowest elevations. Increases at higher elevations were not consistent. The retreats occurred across a broad spectrum of species, from predominantly lowland to predominantly highland. Because deforestation showed no relationship with species retreats, we contend that a warming climate is the most parsimonious explanation for such shifts.

Improved Fracture Segmentation from Unwrapped Drill-Core Images Using an Innovative Two-Stage Segmentation Approach - Fatimah Alzubaidi; Harikrishnan Nalinakumar; Stuart R. Clark; Jan Erik Lie; Peyman Mostaghimi; Ryan T. Armstrong (Mathematical Geosciences, 2023)
While machine learning (ML) provides a great tool for image analysis, obtaining accurate fracture segmentation from high-resolution core images is challenging. A major reason is that the segmentation quality of large and detailed objects, such as fractures, is limited by the capacity of the segmentation branch. This challenge can be seen in the Mask Region-based Convolutional Neural Network (Mask R-CNN), which is a common and well-validated instance segmentation model. This study proposes a two-stage segmentation approach using Mask R-CNN to improve fracture segmentation from unwrapped-core images. Two CNN models are used: the first model processes full-size unwrapped-core images to detect and segment fractures; the second model performs a more detailed segmentation by processing smaller regions of the images that include the fractures detected by the first model. In addition, the procedure uses a new architecture of Mask R-CNN with a point-based rendering (PointRend) neural network module that can increase segmentation accuracy. The method is evaluated on approximately 47 m of core from four boreholes and results in an improvement to previous fracture segmentation methods. It achieves an increase in the average intersection over union of approximately 27% from the baseline (one-stage segmentation with standard Mask R-CNN). The enhanced fracture segmentation provides a mean for obtaining an accurate fracture aperture with an average error of less than 1 mm, which represents a reduction of 0.5 mm from the baseline method. This work presents a novel contribution towards developing an ML-based workflow for core-image analysis.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Perfluoroalkyl substances exposure in firefighters: Sources and implications - Paul E. Rosenfeld; Kenneth R. Spaeth; Linda L. Remy; Vera Byers; Stuart A. Muerth; Ryan C. Hallman; Jasmine Summers-Evans; Sofia Barker (Environmental Research, 2023)

Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

Tree crown damage and its effects on forest carbon cycling in a tropical forest - Jessica F. Needham; Gabriel Arellano; Stuart J. Davies; Rosie A. Fisher; Valerie Hammer; Ryan G. Knox; David Mitre; Helene C. Muller‐Landau; Daniel Zuleta; Charlie D. Koven (Global Change Biology, 2022)
Crown damage can account for over 23% of canopy biomass turnover in tropical forests and is a strong predictor of tree mortality; yet, it is not typically represented in vegetation models. We incorporate crown damage into the Functionally Assembled Terrestrial Ecosystem Simulator (FATES), to evaluate how lags between damage and tree recovery or death alter demographic rates and patterns of carbon turnover. We represent crown damage as a reduction in a tree's crown area and leaf and branch biomass, and allow associated variation in the ratio of aboveground to belowground plant tissue. We compare simulations with crown damage to simulations with equivalent instant increases in mortality and benchmark results against data from Barro Colorado Island (BCI), Panama. In FATES, crown damage causes decreases in growth rates that match observations from BCI. Crown damage leads to increases in carbon starvation mortality in FATES, but only in configurations with high root respiration and decreases in carbon storage following damage. Crown damage also alters competitive dynamics, as plant functional types that can recover from crown damage outcompete those that cannot. This is a first exploration of the trade‐off between the additional complexity of the novel crown damage module and improved predictive capabilities. At BCI, a tropical forest that does not experience high levels of disturbance, both the crown damage simulations and simulations with equivalent increases in mortality does a reasonable job of capturing observations. The crown damage module provides functionality for exploring dynamics in forests with more extreme disturbances such as cyclones and for capturing the synergistic effects of disturbances that overlap in space and time.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Development of a Comparison Framework for Evaluating Environmental Contours of Extreme Sea States - Aubrey Eckert; Nevin Martin; Ryan G. Coe; Bibiana Seng; Zacharia Stuart; Zachary Morrell (Journal of Marine Science and Engineering, 2020)
Environmental contours of extreme sea states are often utilized for the purposes of reliability-based offshore design. Many methods have been proposed to estimate environmental contours of extreme sea states, including, but not limited to, the traditional inverse first-order reliability method (I-FORM) and subsequent modifications, copula methods, and Monte Carlo methods. These methods differ in terms of both the methodology selected for defining the joint distribution of sea state parameters and in the method used to construct the environmental contour from the joint distribution. It is often difficult to compare the results of proposed methods to determine which method should be used for a particular application or geographical region. The comparison of the predictions from various contour methods at a single site and across many sites is important to making environmental contours of extreme sea states useful in practice. The goal of this paper is to develop a comparison framework for evaluating methods for developing environmental contours of extreme sea states. This paper develops generalized metrics for comparing the performance of contour methods to one another across a collection of study sites, and applies these metrics and methods to develop conclusions about trends in the wave resource across geographic locations, as demonstrated for a pilot dataset. These proposed metrics and methods are intended to judge the environmental contours themselves relative to other contour methods, and are thus agnostic to a specific device, structure, or field of application. The metrics developed and applied in this paper include measures of predictive accuracy, physical validity, and aggregated temporal performance that can be used to both assess contour methods and provide recommendations for the use of certain methods in various geographical regions. The application and aggregation of the metrics proposed in this paper outline a comparison framework for environmental contour methods that can be applied to support design analysis workflows for offshore structures. This comparison framework could be extended in future work to include additional metrics of interest, potentially including those to address issues pertinent to a specific application area or analysis discipline, such as metrics related to structural response across contour methods or additional physics-based metrics based on wave dynamics.

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

Using metapopulation theory for practical conservation of mangrove endemic birds - Ryan Huang; Stuart L. Pimm; Chandra Giri (Conservation Biology, 2020)
As a landscape becomes increasingly fragmented through habitat loss, the individual patches become smaller and more isolated and thus less likely to sustain a local population. Metapopulation theory is appropriate for analyzing fragmented landscapes because it combines empirical landscape features with species‐specific information to produce direct information on population extinction risks. This approach contrasts with descriptions of habitat fragments, which provide only indirect information on risk. Combining a spatially explicit metapopulation model with empirical data on endemic species’ ranges and maps of habitat cover, we calculated the metapopulation capacity—a measure of a landscape's ability to sustain a metapopulation. Mangroves provide an ideal model landscape because they are of conservation concern and their patch boundaries are easily delineated. For 2000–20015, we calculated global metapopulation capacity for 99 metapopulations of 32 different bird species endemic to mangroves. Northern Australia and Southeast Asia had the highest richness of mangrove endemic birds. The Caribbean, Pacific coast of Central America, Madagascar, Borneo, and isolated patches in Southeast Asia in Myanmar and Malaysia had the highest metapopulation losses. Regions with the highest loss of habitat area were not necessarily those with the highest loss of metapopulation capacity. Often, it was not a matter of how much, but how the habitat was lost. Our method can be used by managers to evaluate and prioritize a landscape for metapopulation persistence.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

A test of an antipredatory function of conspicuous plastron coloration in hatchling turtles - Beth A. Reinke; Ryan Calsbeek; Devi Stuart-Fox (Evolutionary Ecology, 2017)

Development of a Global Kinetic Model for a Commercial Lean NOx Trap Automotive Catalyst Based on Laboratory Measurements - Mahsa Rafigh; Ryan Dudgeon; Josh Pihl; Stuart Daw; Richard Blint; Syed Wahiduzzaman (Emission Control Science and Technology, 2017)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Particulate nutrient fluxes over a fringing coral reef: Source‐sink dynamics inferred from carbon to nitrogen ratios and stable isotopes - Alex S. J. Wyatt; Ryan J. Lowe; Stuart Humphries; Anya M. Waite (Limnology and Oceanography, 2013)
We examined spatial and temporal variations in particulate organic matter (POM) dynamics over a fringing coral reef (Ningaloo Reef) in Western Australia during the austral autumn and spring. Total POM concentrations generally did not differ between seasons or reef zones, but the composition of POM, in terms of carbon isotope ratios ( δ 13 C‐POM), carbon to nitrogen ratios (C : N), and fatty acids, changed consistently in water flowing across the reef. Both δ 13 C‐POM and C : N increased from the fore reef to the reef flat and lagoon, −23.0‰ to −20.1‰ and 7.31 to 8.34, respectively. Average rates of net POM uptake by the reef community were highest over the reef crest (4 to 30 mmol N m −2 d −1 and 6 to 130 mmol C m −2 d −1 ), with a Bayesian isotope model confirming independent measurements of high uptake rates of allochthonous POM (oceanic phyto‐ and zooplankton). In contrast, over the reef flat, net release of POM was observed (−4 to −5 mmol N m −2 d −1 and −50 mmol C m −2 d −1 ), with gross release rates (estimated as −6 to −8 mmol N m −2 d −1 and −30 to −90 mmol C m −2 d −1 ) indicating that the release of autochthonous POM may be of similar magnitude to allochthonous uptake. Examining POM dynamics in terms of gross fluxes reinforces the dependence of coral reef systems on oceanographic processes for allochthonous POM supply, as well as highlighting the potential for autochthonous POM production to supply nutrients to benthic and pelagic communities downstream.

Growth line deposition and variability in growth of two circumpolar bivalves (Serripes groenlandicus, and Clinocardium ciliatum) - William G. Ambrose; Paul E. Renaud; William L. Locke; Finlo R. Cottier; Jørgen Berge; Michael L. Carroll; Benjamin Levin; Stuart Ryan (Polar Biology, 2012)

Oceanographic forcing of nutrient uptake and release over a fringing coral reef - Alex S. J. Wyatt; James L. Falter; Ryan J. Lowe; Stuart Humphries; Anya M. Waite (Limnology and Oceanography, 2012)
Nitrate and nitrite (NO x ) and phosphate (PO 4 ) dynamics over Ningaloo Reef, Western Australia, are shown to depend on oceanographic forcing of coupled mass transfer limited (MTL) gross uptake and gross release from remineralized oceanic particulate organic matter (POM). Estimates of gross release rates increased significantly with increasing POM uptake and were of the same order as gross uptake rates. Gross uptake rates increased significantly with increasing oceanic concentrations and wave energy dissipation, were 35–80% higher over the reef crest (7–9 mmol NO x m −2 d −1 and 4–5 mmol PO 4 m −2 d −1 ), and were significantly correlated with independent estimates of POM‐mediated gross NO x uptake, supporting both MTL uptake and the strong role of oceanic POM supply. The relative supply of NO x and POM was linked to the seasonal dynamics of a regional current system. In late spring, upwelling associated with seasonally strong equator‐ward winds led to increased NO x concentrations (0.71 ± 0.2 µmol L −1 ), POM x and the reef was a net nutrient sink (5390 mmol NO x m −1 d −1 and 270 mmol PO 4 m −1 d −1 ). In contrast, during the autumn, NO x was low (0.16 ± 0.06 µmol L −1 ), but POM > NO x and the reef was a net nutrient source (−7060 mmol NO x m −1 d −1 and −730 mmol PO 4 m −1 d −1 ). The autumn enhancement of oceanic POM supply to the reef can be attributed to a regional phytoplankton bloom associated with acceleration of the oligotrophic Leeuwin Current, which may result in a significant supply of dissolved nutrients to downstream communities.

Total mercury loadings in sediment from gold mining and conservation areas in Guyana - Joniqua Howard; Maya A. Trotz; Ken Thomas; Erlande Omisca; Hong Ting Chiu; Trina Halfhide; Fenda Akiwumi; Ryan Michael; Amy L. Stuart (Environmental Monitoring and Assessment, 2011)

Adipokine expression and secretion by canine adipocytes: stimulation of inflammatory adipokine production by LPS and TNFα - Vivien H. Ryan; Alexander J. German; I. Stuart Wood; Leif Hunter; Penelope Morris; Paul Trayhurn (Pflügers Archiv - European Journal of Physiology, 2010)

Effect of body tilt angle on fatigue and EMG activities in lower limbs during cycling - Mikel Egaña; Katie Ryan; Stuart A. Warmington; Simon Green (European Journal of Applied Physiology, 2010)

Evidence for structuring of bacterial community composition by organic carbon source in temperate lakes - Stuart E. Jones; Ryan J. Newton; Katherine D. McMahon (Environmental Microbiology, 2009)
Summary Water entering lakes from the surrounding watershed often delivers large amounts of terrestrial‐derived dissolved organic carbon (DOC) that can contribute to aquatic bacterial production. However, research suggests that phytoplankton‐derived DOC is more labile than its terrestrial counterpart, owing to microbial processing of terrestrial‐derived DOC along its flow path to surface waters. The ratio of water colour (absorbance at 440 nm) to chlorophyll a has been suggested as a simple measure of the relative contribution of terrestrial and aquatic primary production to aquatic secondary production. To explore the correlation between primary DOC source and the occurrence of bacterial taxonomic groups, we conducted a survey of bacterial 16S rRNA gene composition in 15 lakes positioned along a water colour : chlorophyll a gradient. Our goal was to identify bacterial taxa occurrence patterns along the colour : chlorophyll a gradient that may indicate a competitive advantage for bacterial taxa using terrestrial or aquatic carbon. We observed a large number of bacterial taxa occurrence patterns suggestive of carbon substrate niche partitioning, especially when relatively highly resolved taxonomic groups were considered. Our survey supports the hypothesis that bacterial taxa partition along a carbon substrate source gradient and highlights carbon source–bacterial interactions that should be explored further.

Interannual dynamics and phenology of bacterial communities in a eutrophic lake - Ashley Shade; Angela D. Kent; Stuart E. Jones; Ryan J. Newton; Eric W. Triplett; Katherine D. McMahon (Limnology and Oceanography, 2007)
We investigated patterns of intra‐ and interannual change in pelagic bacterial community composition (BCC, assessed using automated ribosomal intergenic spacer analysis) over six years in eutrophic Lake Mendota, Wisconsin. A regular phenology was repeated across years, implying that freshwater bacterial communities are more predictable in their dynamics than previously thought. Seasonal events, such as water column mixing and trends in water temperature, were most strongly related to BCC variation. Communities became progressively less similar across years between the months of May and September, when the lake was thermally stratified. Dissolved oxygen and nitrate + nitrite concentrations were highly correlated to BCC change within and across seasons. The relationship between BCC and seasonal drivers suggests that trajectories of community change observed over long time series will reflect large‐scale climate variation.

Experimental manipulations of microbial food web interactions in a humic lake: shifting biological drivers of bacterial community structure - Angela D. Kent; Stuart E. Jones; George H. Lauster; James M. Graham; Ryan J. Newton; Katherine D. McMahon (Environmental Microbiology, 2006)
Summary A previous multiyear study observed correlations between bacterioplankton community composition (BCC) and abundance and the dynamics of phytoplankton populations and bacterivorous grazers in a humic lake. These observations generated hypotheses about the importance of trophic interactions (both top‐down and bottom‐up) for structuring bacterial communities in this lake, which were tested using two multifactorial food web manipulation experiments that separately manipulated the intensity of grazing and the composition of the phytoplankton community. Our results, combined with field observations, suggest that a hierarchy of drivers structures bacterial communities in this lake. While other studies have noted links between aggregate measures of phytoplankton and bacterioplankton communities, we demonstrate here correlations between succession of phytoplankton assemblages and BCC as assessed by automated ribosomal intergenic spacer analysis (ARISA). We used a novel approach linking community ARISA data to phylogenetic assignments from sequence analysis of 16S rRNA gene clone libraries to examine the responses of specific bacterial phylotypes to the experimental manipulations. The synchronous dynamics of these populations suggests that primary producers may mediate BCC and diversity through labile organic matter production, which evolves in quality and quantity during phytoplankton succession. Superimposed on this resource‐mediated control of BCC are brief periods of intense bacterivory that impact bacterial abundance and composition.

Facial Skin Surface Temperature Changes During a “Concealed Information” Test - Dean A. Pollina; Andrew B. Dollins; Stuart M. Senter; Troy E. Brown; Ioannis Pavlidis; James A. Levine; Andrew H. Ryan (Annals of Biomedical Engineering, 2006)

Drainage Size, Stream Intermittency, and Ecosystem Function in a Sonoran Desert Landscape - Ryan A. Sponseller; Stuart G. Fisher (Ecosystems, 2006)